Sustainable tourism practices in the Mediterranean - Tüzün, Ipek Kalemci; Ergül, Mehmet; Johnson, Colin (Contemporary geographies of leisure, tourism and mobility, 2020)
"Sustainable Tourism Practices in the Mediterranean showcases and examines the current and future trends in sustainable tourism in this popular region where tourism is one of the leading determinants of economic development. This volume examines the effects of specific recent events including terrorism, financial crises and various political changes in the Mediterranean region. Looking at a range of destinations; island and mainland, urban and rural, summer and winter and emergent and declining zones, it provides a comprehensive overview of this area. It also draws on a number of wide-ranging themes such as gastronomy, (corporate) social responsibility, entrepreneurship, ethical issues, service quality, health and the slow city, offering an insightful study of the challenges the Mediterranean region faces and the sustainable practices that can be implemented in order to overcome them. Written by leading academics in the field, this book will be of great interest to upper-level students, researchers and academics in Tourism, Development Studies and Geography"--